Role of calcium phosphate product in maturation and patency of native arteriovenous fistula in end stage renal disease patients in Kelantan - Fakri, Azimah (2017)
There has been an increasing trend of end stage renal disease patients requiring haemodialysis treatment worldwide. Vascular access remains the key component of haemodialysis treatment, unfortunately, the maintenance of this access remains a challenging problem. The maturity of arteriovenous fistula is influenced by variable factors such as age, presence of atherosclerosis, vascular calcification as result from calcium phosphate product and uremia. This study had been done due to lack of study and evidence on effect of calcium phosphate product with correlation of calcium deposition in intima layer in determining AVF maturation and patency. This prospective study was performed in Chronic Kidney Disease (CKD) Resource Center, Hospital Universiti Sains Malaysia between Jan 2016 to May 2016. One hundred and twenty one patients were eligible for this study who underwent AVF creation under Reconstructive Science Unit HUSM. Patients above 18 years old with End Stage Renal Disease requiring regular hemodialysis were included in this study with no previous intervention of the central vein. Exclusion criteria included peripheral vascular disease, central venous stenosis, vascular access site deformity and vasculitic disease. Among the selected 121 subjects, 59 (48.8%) and 62 (51.2%) achieved normal and delayed maturation respectively. The mean age for normal AVF maturation was 55.7 years, while delayed arteriovenous maturation was 58.5 years. Calcium phosphate product was not associated with delayed AVF maturation (p value 0.53); with lower mean (SD) calciumphosphate product was observed in delayed mature AVF, 3.16 mmol/L (0.99) compare to normal mature AVF group, 3.35 mmol/L (1.28). There was no association between calcium deposition and delayed maturation of AVF (p value = 0.30). In delayed AVF group, there were 13 samples (21.0%) showed calcium deposition, whereas in normal maturation AVF group, there were 15 samples (25.0%) showed calcium deposition. Correlation between calcium depositions in intima layer with delayed maturation of AVF also showed no significant result with p value 0.59. In conclusion, calcium phosphate product and calcium deposition based on tissue biopsy have no effect on AVF maturation and patency. However few considerations for confounding factors and limitation need to be taken.